Pengaruh Penyelesaian Pembiayaan Macet berdasarkan Ketentuan Fatwa Dan dan Kompilasi Hukum Ekonomi Syariah - Nurul Iman (CV. Creative Tugu Pena, 2024)
Legal arrangements for settling bad debts at Islamic banks in accordance with the Sharia Banking Act can be through litigation and non-litigation channels. The settlement of litigation path is by submitting a lawsuit to the Religious Court, while the settlement through non-litigation channels is carried out through Basyarnas. The process of resolving bad debts based on sharia principles refers to banking legal provisions that are adjusted to the provisions of the DSN Fatwa and Compilation of Sharia Economic Law. The absolute competence of the Religious Courts in resolving financing is stalled on Islamic banks, which are still ambiquity. Because the absolute authority of the Religious Courts in resolving sharia banking disputes is then reduced after the issuance of the Sharia Banking Act which provides an opportunity for the General Court to resolve sharia banking disputes in accordance with the provisions of Article 52 paragraph (2) of the Sharia Banking Act.